PERANAN GURU IPS DALAM MEMBENTUK KARAKTER DISIPLIN PESERTA DIDIKKELAS VIII DI MTS MIFTAHUL ULUM MEMPAWAH - Mustamiin Mustamiin; Okianna Okianna; Heni Kuswanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
Abstractthe title of this research is "The role of social studies teachers in influencing the disciplinecharacter of class VIII students at MTs Miftahul Ulum Mempawah". The generalproblem discussed in this research is how social studies teachers influenced the disciplinecharacter of students in class VIII. The purpose of this study is to determine how social studiesteachers' abilities as mentors, leaders, and supervisors influence students' disciplined behavior.A qualitative technique with a descriptive strategy was used in this study. The approach usedis a qualitative approach with a descriptive method the technique used in data collection areinterview, observation and documentation techniques. This study's qualitative analysis isbased on input from six individuals: a social studies teacher, a guidance and counselingteacher, homeroom teacher for class VIII guardian, and three students who constantly breakdisciplinary rules. The findings of this study show that social studies teachers influenced thediscipline character of class VIII students. The role of the social studies teacher as a supervisoris the existence of guidance books and special books owned by social studies teachers andthere are several guidance programs such as the morning ceremony program and religiousprograms. The social studies teacher's role as a leader can be seen in the teacher's role as amoral role model for students and teachers who always comply school rules, as well as thesocial studies teacher's role as a supervisor, which entails strict supervision of students whoconstantly break disciplinary rules.Keywords: Social Studies Teacher's Role, Character, Discipline